Psychosocial predictors of body mass index at late childhood: A longitudinal investigation. (June 2014) - Holm-Denoma, Jill M; Smith, April; Lewinsohn, Peter M; Pettit, Jeremy W
Little is known about the psychosocial circumstances under which children develop excessive body mass. A community sample was followed up from age 2–10 years to determine which early problems were predictive of increased body mass index. Hypothesized mediators (i.e. eating habits, physical activity, and "screen time") were also examined. After controlling for parental psychopathology, family income, child's gender, and child's body mass index, externalizing behaviors, aggressive behaviors, and anger predicted a relatively high body mass index. Exploratory analyses did not support hypothesized mediators, although low power was an issue.